Comprehensive investigation of the role of Nb on the oxidation kinetics of Zr-Nb alloys. (15th July 2019) - Moorehead, Michael; Yu, Zefeng; Borrel, Léo; Hu, Jing; Cai, Zhonghou; Couet, Adrien
Highlights: Zr-Nb alloys show different oxidation kinetics due to Nb content and distribution. Synchrotron is used to observe Nb oxidation states across metal/oxide interface. Nb leeches out of β-Zr into the oxide rapidly upon oxidation of the precipitate. C4 model is used to relate Nb content and distribution with oxidation kinetics. Modeling and characterization reveal mechanism for different oxidation kinetics. Abstract: Waterside corrosion of zirconium alloys is currently the life-limiting degradation mechanism of fuel elements in pressurized-water reactor (PWR) systems. Today, PWRs use Zr-Nb fuel cladding designed to limit oxidation and hydrogen pickup. However, oxidation kinetics of Zr-Nb alloys can vary substantially depending on the Nb content and distribution, even in alloys of the same composition but different heat treatments. To elucidate the role of Nb on Zr-Nb oxidation kinetics and improve the fundamental understanding of Zr-Nb corrosion, nano-beam X-ray absorption near-edge spectroscopy (XANES), transmission electron microscopy (TEM), and application of the Coupled-Current Charge-Compensation (C4) Model have been performed in concert.